Modelo de autômatos celulares para o vírus da Herpes Simplex - HSV - Miranda, Luiza Mayara Santos (2022)
Present in approximately two thirds of the world’s population, the herpes simplex virus has been causing problems for humanity since ancient times. However, we do not know completely everything about the virus, despite the various treatments and stu dies, there is currently no cure and the possibility of a vaccine is a future perspective. Primary infection happens when the virus comes into contact with epithelial tissue and is permanent. Studying the behavior of the virus in the organism using the cellular au tomata model, simulations were created in Python modifying important parameters for infection such as the time the immune system takes to recognize the virus z, the proba bility of new cells being born in the environment of infection, reinfections and behavior without the presence of defense T cells. The results obtained from these parameter variations are in good agreement with literature reports, i.e. without an immune sys tem, the virus in the body behaves aggressively, which may represent the beginning of herpes virus infections in the human system. The immune system depends on z to recognize the virus and the infection is greater when T cells are slow to recognize the virus. When new cells are born, there is the possibility of being infected again if their neighboring cells are infected, which interferes with the results of the simulations. For reactivation of the virus in the host when the immune system is weakened, there is a likelihood of symptomatic infections reoccurring, but the body takes less time to recognize the virus and eliminate them.